2014
DOI: 10.1007/978-3-319-08171-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms Implemented for Cancer Gene Searching and Classifications

Abstract: Abstract. Understanding the gene expression is an important factor to cancer diagnosis. One target of this understanding is implementing cancer gene search and classification methods. However, cancer gene search and classification is a challenge in that there is no an obvious exact algorithm that can be implemented individually for various cancer cells. In this paper a research is conducted through the most common top ranked algorithms implemented for cancer gene search and classification, and how they are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Also, the authors in [55] exposed the highest accuracy for colon cancer classification found by KNN (K-Nearest Neighbors) and Neural Network classifier among other classification algorithms, however they claimed out that other optimization techniques can be added to classification algorithms. Many algorithms have been implemented for the selection and classification of cancer genes [29]. These include Genetic Algorithm (GA), Particle Swarm Optimization (PSO), Analysis of Variance (ANOVA), Information Gain (IG), Relief Algorithm (RA), and t-statistics (TA).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the authors in [55] exposed the highest accuracy for colon cancer classification found by KNN (K-Nearest Neighbors) and Neural Network classifier among other classification algorithms, however they claimed out that other optimization techniques can be added to classification algorithms. Many algorithms have been implemented for the selection and classification of cancer genes [29]. These include Genetic Algorithm (GA), Particle Swarm Optimization (PSO), Analysis of Variance (ANOVA), Information Gain (IG), Relief Algorithm (RA), and t-statistics (TA).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…These include Genetic Algorithm (GA), Particle Swarm Optimization (PSO), Analysis of Variance (ANOVA), Information Gain (IG), Relief Algorithm (RA), and t-statistics (TA). The classification algorithms that exhibit good performance are Support Vector Machine (SVM), K-Nearest Neighbors (KNN), Naïve Bayes, Neural Networks (NN), and Decision Tree (DT) [29]. Many studies have been conducted to study the process of cancer classification using microarray genetic data, including colon cancer.…”
Section: Background and Literature Reviewmentioning
confidence: 99%